The Use of STEM Approaches To Improve Formula Derivation Steps in Material Science and Engineering Programmes at Higher Education Institutions - Darko, Charles (European Scientific Journal, ESJ, 2021)
Many complex formula derivation steps found within material science and engineering programmes are essential skill-developing activities that enhance students’ learning. Most students lack the required mathematical knowledge to fully comprehend some of those derivation steps. This work involves the development of a framework for clarifying some of the original derivations by adding further mathematical steps that support students’ constructive and cognitive learning. Modifications were made on the theoretical tensile strength derivations, the Maxwell’s and the Voigt-Kelvin’s models. The aim is to facilitate students’ learning and help them acquire transferable skills when solving other material science and engineering problems. Students benefited from the activities in two folds; firstly, they understood the mathematical reasons behind each derivation step and secondly, their study periods were reduced. These activities provide a platform for widening STEM activities at higher education institutions. The ongoing work will look at other important formula derivation steps within material science and engineering.